Increase of cooperation permitted by computers in a distance education environment - Ivan Ferrer Maia; Carla Lopes Rodriguez; Flaminio de Oliveira Rangel; José Armando Valente; Sandro Palhão (Faculdade de Medicina de Botucatu (Unesp), 2007)
This article analyzes part of the results of a social research program developed along with neighborhood health agents of São Marcos and Santa Mônica in Campinas, state of São Paulo. It was a longitudinal study carried out over a period of a year and a half carried out throughout three phases: face-to-face, intermediary stage and pure distance work. In this article we solely discuss the activities during the face-to-face phase, whereby agents learnt how to use the computer and the TelEduc2 system. We opted to apply qualitative observation given that the main objective of this research was to identify Piaget's developmental stages within the context of the agents' capacity to understand tangible and intangible aspects of the technological universe. This relationship was possible when the subjects began to interact with basic elements of the computer and with TelEduc. After overcoming a state of anomia and understanding the tools that allowed a heteronomous attitude, agents used resources allowing them to enter a relationship of cooperation.